Biosynthesis of CoNPs: An Overview - Saini, Vaibhav; Thakur, Ajay; Verma, Monika; Bharti, Ruchi; Sharma, Renu (Orbital: The Electronic Journal of Chemistry, 2024)
Nanotechnology encompasses the scientific exploration of material characteristics at the nanoscale, with a profound reliance on factors such as size, shape, and morphology. Its far-reaching potential holds the capacity to reshape numerous global industries and technologies, including healthcare, electronics, cosmetics, chemicals, energy, and composites. Nonetheless, conventional synthesis methods, predominantly chemical and physical, are progressively revealing their limitations over time. Consequently, a pressing imperative arises to investigate alternative strategies that enable the fabrication of NPs devoid of environmental hazards. Developing eco-friendly approaches for Nanoparticles (NPs) synthesis stands as a pivotal catalyst in advancing the principles of green chemistry. Presently, plant-based extraction methods have effectively demonstrated their efficacy in the synthesis of Cobalt nanoparticles (CoNPs). This succinct review presents an inclusive overview of the methodologies, advantages, and recent research endeavors about producing CoNPs employing green synthesis approaches involving plants, bacteria, and fungi.